SOCIOLOGICAL ANALYSIS OF STUDENT SOCIAL ACTIVITY IN HIGHER EDUCATION INSTITUTIONS - Pavlik , Elena; Khakimov , Orzikul (Effective scientific journals, 2026)
Student social activity represents a crucial indicator of civic engagement and social participation in modern societies. Universities play a central role in shaping students’ social behavior, values, and engagement in community life. In recent years, increasing attention has been paid to understanding the factors influencing students’ participation in social initiatives, volunteer programs, and civic organizations. The purpose of this study is to examine the sociological determinants of student social activity in higher education institutions. The research applies a mixed-method approach combining survey analysis, statistical modeling, and regression analysis. Data were collected from 200 university students through structured questionnaires measuring motivation level, digital engagement, and campus environment factors. The results indicate that student motivation and institutional support significantly influence the level of social activity. Regression analysis demonstrates that motivation (β = 0.47) and campus environment (β = 0.45) are the strongest predictors of student social participation. The findings suggest that universities can significantly enhance social engagement by creating supportive institutional environments and encouraging student-led initiatives. The study contributes to contemporary youth sociology by proposing an empirical framework for analyzing student social participation in higher education contexts.